THROMBOCYTOPENIA AT DIFFERENT STAGES OF PREGNANCY - S Elhassade, Amal; Ben Nasser, Alisa (International Journal of Clinical and Biomedical Research, 2016)
Background: Thrombocytopenia is a common finding in pregnancy, occurring in approximately 10 - 16% of women. The normal range of platelet counts decreases, and it is not uncommon for the platelet counts to decrease as pregnancy progresses. Lower platelet count observed in the pregnant are due to normal physiologic changes, and has many common causes including gestational thrombocytopenia, viral and bacterial infection and preeclampsia complicated by hemolysis. Objective: the objective was to investigate thrombocytopenia during different stages of pregnancy. Materials and methods: Sixty three pregnant women were included in this study from different clinic in Derna city. Mean age (28 ± 1.4) year with a range (20 ± 1.4) year. At the same time a group of Sixty three healthy non pregnant women mean age ( 29 ± 2.2 ) with a range ( 23 - 45 ) year to compare platelets count between them. By automated cell counter platelets from all pregnant and non pregnant were estimated. Results: Pregnant women had lower platelets count (mean 193— 109/l) as compared to healthy non pregnant women (mean 250— 109/l). There was significant decrease in platelet count in pregnant as compare with non pregnant P < 0.001. Conclusion: Platelet counts were performed on sixty three normal patients at different stages of pregnancy. Patients with complications of pregnancy known to influence the platelet count were excluded from the study. There was significant decrease in platelet count during pregnancy. KEYWORDS: Thrombocytopenia; Gestational thrombocytopenia; Idiopathic thrombocytopenia; Pregnancy